Penyuluhan kesehatan mengenai metode kontrasepsi pada wanita usia subur (WUS) di wilayah terdampak banjir - Aruan, Lasria Yolivia; Manullang, Rasmi; Nadeak, Yasrida; Novita, Plora; Isabella, Nova; Padilla, Erin; Aslamia, Saibatul (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Floods are a frequent disaster and have the potential to negatively impact health care services, including reproductive health. Women of childbearing age in flood-affected areas are at risk of limited access to contraceptive information and services, increasing the risk of unplanned pregnancies. Purpose: This community service activity aims to increase the knowledge and understanding of in flood-affected areas regarding contraceptive methods. Method: The activity was conducted in November 2025 in Bandar Klippa Village, a flood-affected area. Forty women of childbearing age and health workers in the Bandar Klippa Village area participated as respondents. This activity used a promotive-educational approach to increase women of childbearing age's knowledge regarding reproductive health, particularly regarding appropriate, safe, and healthy contraceptive method choices. Respondents' knowledge levels were measured using questionnaires administered before and after the educational activity (pre-test) and after the educational activity (post-test). Evaluation of the activity was conducted by observing the increase in respondents' knowledge between before and after the educational activity. Mentoring and observation were conducted to assess respondents' active role during the activity, including their level of participation, active participation in activities, attendance, and interest in contraceptive use. Results: Obtaining data that the average age of respondents is 31.55 years and most respondents are in the age range of 26-30 years, namely 12 people (30.0%). A total of 34 respondents understand the types of contraception, 36 respondents were also actively involved in discussion activities during the activity, 32 respondents had an interest in using contraception, and all respondents followed the activity to completion. Table 2 shows that the level of knowledge of respondents is in the good category, 18 people (45%) in the sufficient category, and 12 people (30%) in the poor category. There is a change in the proportion of respondents' level of knowledge in the good category from 10 people (25%) before the educational activity to 30 people (75%) after the educational activity. Conclusion: Community service activities providing contraceptive counseling to women of childbearing age in flood-affected areas have proven effective and significantly increased their knowledge and ability to recognize various contraceptive methods. These activities also made a positive contribution to the community, increasing motivation, participation, and interest in appropriate, safe, and healthy contraceptive use. Suggestion: Sustainable reproductive health counseling involving health cadres, medical personnel, and village government support is needed to ensure that contraceptive information remains available to the community, especially in disaster-prone areas. Keywords: Contraceptive methods; Health counseling; Impact of flooding; Reproductive health; Women of childbearing age Pendahuluan: Banjir merupakan bencana yang sering terjadi dan berpotensi memiliki dampak buruk terhadap pelayanan pada fasilitas kesehatan menjadi terganggu, termasuk kesehatan reproduksi. Wanita usia subur (WUS) di wilayah terdampak banjir berisiko mengalami keterbatasan akses informasi dan layanan kontrasepsi, sehingga meningkatkan risiko kehamilan tidak direncanakan. Tujuan: Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan pengetahuan dan pemahaman WUS di wilayah terdampak banjir mengenai metode kontrasepsi. Metode: Kegiatan dilaksanakan pada bulan November 2025 di Desa Bandar Klippa, yang merupakan wilayah terdampak banjir. Melibatkan 40 wanita usia subur untuk menjadi responden dan tenaga kesehatan wilayah Desa Bandar Klippa. Kegiatan ini menggunakan pendekatan promotif edukatif dalam meningkatkan pengetahuan wanita usia subur terkait kesehatan reproduksi, khususnya mengenai pilihan metode kontrasepsi yang sesuai, aman, dan sehat. Pengukuran tingkat pengetahuan responden menggunakan kuesioner yang diberikan sebelum kegiatan edukasi (pre-test) dan sesudah kegiatan edukasi (post-test). Evaluasi kegiatan dilakukan dengan melihat peningkatan pengetahuan responden antara sebelum kegiatan edukasi dan sesudah kegiatan edukasi. Pendampingan dan observasi dilakukan untuk melihat peran aktif responden selama kegiatan dilaksanakan meliputi tingkat partisipasi, keaktifan dalam mengikuti kegiatan, kehadiran dan keminatan penggunaan kontrasepsi. Hasil: Mendapatkan data bahwa rata-rata usia responden adalah 31.55 tahun dan sebagian besar responden berada di rentang usia 26-30 tahun yaitu sebanyak 12 orang (30.0%). Sebanyak 34 responden memahami jenis kontrasepsi, sebanyak 36 responden juga terlibat aktif dalam kegiatan diskusi selama kegiatan, sebanyak 32 responden memiliki keminatan untuk menggunakan kontrasepsi, dan seluruh responden mengikuti kegiatan hingga selesai. Pada tabel 2 menunjukkan bahwa tingkat pengetahuan responden adalah dalam kategori baik, sebanyak 18 orang (45%) dalam kategori cukup, dan sebanyak 12 orang (30%) dalam kategori kurang. Terdapat perubahan proporsi tingkat pengetahuan responden dalam kategori baik dari sebanyak 10 orang (25%) sebelum kegiatan edukasi menjadi sebanyak 30 orang (75%) setelah kegiatan edukasi. Simpulan: Kegiatan pengabdian kepada masyarakat berupa penyuluhan metode kontrasepsi pada wanita usia subur di wilayah terdampak banjir terbukti efektif dan signifikan dapat meningkatkan pengetahuan dan kemampuan dalam mengenali berbagai metode kontrasepsi. Kegiatan ini juga memberikan kontribusi positif pada masyarakat dan meningkatkan motivasi, partisipasi dan minat penggunaan kontrasepsi yang sesuai, aman, dan sehat. Saran: Diperlukan pelaksanaan penyuluhan kesehatan reproduksi secara berkelanjutan dengan melibatkan kader kesehatan, tenaga medis, serta dukungan pemerintah desa agar informasi kontrasepsi tetap tersedia bagi masyarakat, terutama di wilayah rawan bencana.